Identification of LuxR Family Regulators That Integrate Into Quorum Sensing Circuit in Vibrio parahaemolyticus - Zhong, Xiaojun; Lu, Ranran; Liu, Fuwen; Ye, Jinjie; Zhao, Junyang; Wang, Fei; Yang, Menghua (Frontiers in Microbiology, 2021)
Vibrio parahaemolyticus is one of the most important food-borne pathogens that cause economic and public health problems worldwide. Quorum sensing (QS) is a way for the cell-cell communication between bacteria that controls a wide spectrum of processes and phenotypic behaviors. In this study, we performed a systematic research of LuxR family regulators in V. parahaemolyticus and found that they influence the bacterial growth and biofilm formation. We then established a QS reporter plasmid based on bioluminescence luxCDABE operon of V. harveyi and demonstrated that several LuxR family regulators integrated into QS circuit in V. parahaemolyticus. Thereinto, a novel LuxR family regulator, named RobA, was identified as a global regulator by RNA-sequencing analyses, which affected the transcription of 515 genes in V. parahaemolyticus. Subsequent studies confirmed that RobA regulated the expression of the exopolysaccharides (EPS) synthesis cluster and thus controlled the biofilm formation. In addition, bioluminescence reporter assays showed that RobA plays a key role in the QS circuit by regulating the expression of opaR, aphA, cpsQ-mfpABC, cpsS, and scrO. We further demonstrated that the regulation of RobA to EPS and MfpABC depended on OpaR and CpsQ, which combined the QS signal with bis-(3’-5’)-cyclic dimeric GMP to construct a complex regulatory network of biofilm formation. Our data provided new insights into the bacterial QS mechanisms and biofilm formation in V. parahaemolyticus.